EFEKTIVITAS PENGGUNAAN MEDIA KIRANA DALAM MENINGKATKAN PEMAHAMAN KONSEP MATERI KEBERAGAMAN BUDAYA PADA SISWA KELAS IV SD - fauziyyah, athifah; Andhin Dyas Fitriani; Sendi Fauzi Giwangsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low level of students' conceptual understanding of cultural diversity. The study aimed to determine the effectiveness of KIRANA media in improving students' conceptual understanding of cultural diversity in fourth grade elementary school. One of the reasons for this is the lack of use of learning media that explores students' conceptual understanding. In IPAS learning, the research method used was pre-experimental with a one-group pre-test post-test design. The population in this study was fourth-grade elementary school students in Japara District. The sample in this study was 26 fourth-grade students from one public elementary school in Japara District. The instruments used were pre-test and post-test instruments in the form of 8 essay questions based on indicators of conceptual understanding of cultural diversity material. Data analysis used a mean difference test to assess the effectiveness of the KIRANA media. Based on the mean difference test, significant results were obtained, leading to the acceptance of H₁, indicating a significant difference. Additionally, the improvement in conceptual understanding of cultural diversity material through the KIRANA media was proven by the N-Gain test results, which fell into the high category, and the effectiveness level was in the moderately effective category. Thus, the KIRANA media was proven to be moderately effective in enhancing students' conceptual understanding.